INDIVIDUALIZATION AND DIFFERENTIATION AT TEACHING OF PUPILS WITH COGNITIVE DEVELOPMENT - Svitlana Dmytrivna Yakovleva (Insight: the psychological dimensions of society, 2019)
The article purpose is to stress the importance of individualization and differentiation at teaching of children with cognitive development disorders. The following research methods were applied to achieve this goal: analysis of the problem in the psycho-pedagogical literature, as well as a practical study of individualization and differentiation used at teaching of children with cognitive development disorders. As a result, an attempt is made to distinguish between the concepts of «individualization» and «differentiation» at teaching of children with impaired intelligence. It has been found that these concepts are not synonymous but interdependent and interrelated. Today, there are different approaches to address the problem of differentiation at teaching and, as a result, there are different definitions of the basic concepts of this problem. The main goal of individualization and differentiation used at teaching of children with special educational needs is their development. The objectives of individualization and differentiation are to preserve their individuality, to create a unique personality, which is possible provided the development of functions lying in the «zone of immediate development». For this purpose, corrective work is used that stimulates the compensatory cognitive development of children with cognitive disorders with the aim to correct their developmental defects as much as possible. General psychological patterns of developmental learning is of great importance for defectology, since children with cognitive disorders need pedagogical assistance to fulfil their developmental potentials, and to transform them into such abilities that children can use to master various themes within the educational content. Individualization and differentiation at teaching play the decisive role in this process.The practical aspect of the issue was studied on the basis of a junior special needs school, where children with cognitive development disorders have been studied. The classroom form of education was used with taking into account the peculiarities of each child and application of appropriate educational techniques. Different levels of support for children were used as well as right approaches to their work analyzing and evaluating. Children were divided into several groups according to their typological features and their potential abilities, thus the individual and differential approach was applied.Conclusions. The analysed learning peculiarities of children with cognitive development disorders showed their increased positive attitudes to task completion and more successful mastering of the educational material.